Policy Management in the 5.0 Era in Education Units - Sari, Diah Ayu Puspita; Zahrah, Zahrah; Mubaraq, Muhammad Zaki; Hafidz , Muhammad; Sholeh, Makherus (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2024)
The 5.0 era demands deep digital transformation in all sectors, and education units are no exception. This article aims to discuss policy management in the context of education, especially in the 5.0 era, which is characterized by the integration of technology and humanist approaches in the learning process. The 5.0 era prepares students to face the challenges of the future, and requires educational units to adapt to rapid social and technological changes. This study uses a qualitative method with the Systematic Literature Review (SLR) approach by examining the results of research that have been published in journal articles that discuss the 5.0 era in educational units. The results of the study show that effective policy management in the 5.0 era includes the development of a curriculum that is responsive to industry needs, improving teacher competence through technology-based training, and collaboration between schools, parents and the community. Then, the article identifies the challenges faced by education units in implementing the policy, including resource limitations and resistance to change. It is hoped that these findings can provide insight for stakeholders in formulating better policy management strategies to improve the quality of education in the 5.0 era.